Jaminan Hak Asasi Manusia dalam Peristiwa Manak Salah di Bali - Putu Endra Wijaya Negara; A.A. Gede Oka Parwata (University of Udayana, 2021)
This study aims to determine the arrangement of customary traditions based on Indonesian law and to understand the guarantee of Human Rights in the Manak Salah Tradition in Bali. The method used in research related to human rights assurance in the Manak Salah Tradition in Bali uses normative juridical legal research, using a statutory approach or a statute approach to analyze legal issues in this study. Sources of legal materials in this study consist of primary, secondary, and tertiary legal materials. The results of this study found that human rights guarantee in the Manak Salah Tradition in Bali basically have to be uniform. This is because a tradition will be very difficult to erase, this is because customary law is recognized in the 1945 Constitution of the Republic of Indonesia Article 18B paragraph (2) even though customary law cannot conflict with national law. So that in order to guarantee human rights from the wrong tradition, special arrangements are needed in the form of proper housing facilities, visited by other village krama, provision of MCK facilities, assisted with readiness by all village manners as a whole so as to help ease the burden on the family who is subject to sanctions, help ease the family. Penelitian ini bertujuan untuk mengetahui pengaturan tradisi adat berdasarkan Hukum Indonesia serta memahami jaminan Hak Asasi Manusia (HAM) dalam Tradisi Manak Salah di Bali. Metode yang digunakan dalam penelitian terkait jaminan HAM dalam Tradisi Manak Salah di Bali ini mempergunakan jenis penelitian hukum yuridis normatif, dengan menggunakan pendekatan perundang-undangan atau statute approach dan pendekatan konseptual atau conceptual approach untuk menganalisis isu hukum dalam penelitian ini. Hasil dari studi ini menemukan jika jaminan HAM dalam Tradisi Manak Salah di Bali pada dasarnya harus dilakukan penyeragaman. Hal ini dikarenakan suatu tradisi akan sangat sulit untuk dihapuskan, hal ini dikarenakan hukum adat diakui dalam UUD NRI 1945 Pasal 18B ayat (2) meskipun hukum adat tidak boleh berlawanan dengan hukum positif Indonesia. Sehingga untuk menjamin HAM dari tradisi manak salah diperlukan pengaturan secara khusus berupa fasilitas perumahan yang layak, dikunjungi oleh krama desa yang lain, penyediaan fasilitas MCK, dibantu kesiapannya oleh seluruh krama desa secara keseluruhan sehingga membantu meringankan beban pihak keluarga yang terkena sanksi, membantu meringankan keluarga.